Aortic Aneurysm as a Cause of Dysphonia in a Patient Who Smokes - Bayones, Miguel; Ruiz-Rodríguez, Jose; Sierra, Carlos (Puerto Rico Health Sciences Journal, 2020)
Vocal cord paralysis secondary to a cardiovascular disease is known as Cardiovocal or Ortner’s syndrome. The most common cause of Ortner’s syndrome is atrial dilation due to mitral valvulopathy. Other causes include aneurysms of the thoracic aorta, patent ductus arteriosus, aneurysm of the ductus arteriosus, defects of the interatrial or interventricular septum, among others. Hoarseness might be the only symptom that leads a given individual to consult with a physician. Here we present the case of a 77-year-old male patient with history of diabetes mellitus type 1 and hypertension, whose illness started about a year ago when he presented progressive dysphonia associated with dry cough after food intake without another concomitant symptom. CT studies reported the presence of an aortic aneurism compressing the left recurrent nerve. Patient refused surgical treatment. As of this writing, he remains symptomatic.